Alienação e transcendência: a realidade e o devir humano: um estudo da práxis educativa à luz da teoria da alienação de Marx - Steil, Carlos Alberto (1990)
It is the question here of a study about the theory of alienation in Marx, and of a reflation about the educational practice under the light of this theory. The investigation of the alienation theory in Marx includes a stud~ of the philosophers who preceded him in the building UP of this concept. Three works are privileged in regard to the systematization of this theory in Marx: Economic and philosophical manuscripts of 1844, German ideology, Fundamental elements for the criticism of political economy C'Grundrísse). Dismissing the metaphysical vision which pretends to give alienation an ontological and mystifying signification, Marx takes it as a historical form of human relationship and analyses it in its multiple dimensions. Under the light of the theory of alienation, a criticism of the metaphysical vision of education s undertaken in the 2nd. part of this work, which reduces alienation to a question of cognition, solved in the field of conscience, being surmounted, therefore, within the ambit of education. In opposition to this perspective, stands the notion that a non-alienated conscience can only be thought of as the conscience of an entirely humanized society. Placed in the context of an alienated society, education presents as a possibility, to contribute as a mediation at one time practical an theoretical to overcome alienation, once it articulates itself with the whole of the social and political transforming practices.